Boundary detection capability and influencing factors of electromagnetic resistivity while using drilling tools in a horizontal well - Tian, Yuanshi; Zhu, Jun; Die, Yong; Liu, Limeng; Yue, Can; Wang, Xuanguang; Zhu, Yusha (Frontiers in Earth Science, 2023)
With the increase in the scale of mining in horizontal and highly deviated wells, electromagnetic boundary detection while drilling plays an important role in boundary detection. This paper examines three types of antenna structures commonly used in electromagnetic boundary detection and measurement methods and also performs a numerical simulation of the edge detection capability of the three structures in horizontal wells. The simulation experiment analyzes the influence of formation resistivity contrast, frequency, spacing, and other factors on the capability of edge detection and provides data that supports the design of instrument antenna parameters. The numerical simulation shows that the tilted and orthogonal receiving antennas demonstrate improved performance both in detecting the interface when approaching from high-resistance layers and low-resistance layers. In addition, the capability of boundary detection can be improved by decreasing the frequency and increasing the spacing between the transmitter and receiver.